Output of main nutrients by sunflower plants depending on the variety characteristics, predecessors and rates of chemical fertilizers in the north-eastern Left-bank Forest-Steppe zone of Ukraine - Мельник, А. В.; Троценко, В. І.; Говорун, С. О. (Scientific Progress & Innovations, 2015)
According to the research it was found that fertilizers’ application on sunflower crops caused the cost reduction of nitrogen and potassium per unit yield formation. Application of N30P30K30 results reducing of nitrogen’s consumption to 0,9 kg/ha and potassium to 6,1 kg/t. Application of N60P60K60 reduced the use of nitrogen to 0,9 kg/ha and potassium – to 8,8 kg/ton, compared with the control. Use of phosphorus were unchanged.